Food Calory Intake and Physical Activity in Obesity Risk among College Students in Surabaya City - Lorensia, Amelia; Suryadinata, Rivan Virlando; Tinaka, Adela Juana (Jurnal Kesehatan Masyarakat, 2024)
Productive age is at the peak of its activities, physical activities carried out tend to be heavier than other ages and one of the characteristics of developed countries is a country that has a high level of health, intelligence, and work productivity, which is influenced by nutritional intake and diet. Diet, excess tend to be owned by obesity, obesity is also included in the condition of malnutrition.The research aimed knowing effect of diet and physical activity on the risk of obesity in students at a university in Surabaya.The method used in this study is case control with 152 obese and non obese adult respondents at a university in Surabaya using a 24-hour recall questionnaire, IPAQ for physical activity, and measurement of BMI (body mass index). The results of the study on average food calorie intake in obese adult respondents were higher than non-obese. The most consumed type of food obesity group (60 people) is chicken meat (mean: 348.55 kcal), while the most consumed food non-obese group (60 people) is white rice (mean: 753.71 kcal). The biggest calories consumed in obese groups (34 people) are pizza (1,925.48 kcal), while those that are most consumed by non-obese groups are white rice. The results of statistical analysis using the chi-square test showed that there were significant differences in food intake between obese adult groups and non-obese adult groups (p=0.000). The results of the analysis of physical activity obtained in the obese group showed that most of them had low physical activity (61.84%). Meanwhile, in the non-obese group, most of them had moderate physical activity (55.26%). Based on the results of the analysis with the Chi-Square Test, with P value of 0.047 was obtained (p value 0.05) so that it could be concluded that there was a significant difference in physical activity between the non-obese and obese respondent groups. The average level of physical activity in non-obese is higher than the obese group. By increasing physical activity and reducing food calorie intake, the risk of obesity in adulthood can be reduced.